Checklist of mycoheterotrophic species of the genus Exacum (Gentianaceae) and new species, E. zigomorpha, from northern Vietnam - Averyanov, Leonid V.; Nguyen, Khang Sinh; Nguyen, Hiep Tien (Phytotaxa, 2014)
The paper provides a key for identification and a checklist of mycoheterotrophic species of the genus Exacum, representing a well-defined group of achlorophyllous members of Gentianaceae regarded sometimes in the limits of a separate genus Cotylanthera. One novel species, E. zygomorpha, discovered in northern Vietnam, is described and illustrated as new for science. Among other features the discovered species strikingly differs from its congeners in having distinctly zygomorphic flowers.